PRAESEN STATUS OF FEMALE BALI CATTLE IN THE THIRD TRIMESTER OF PREGNANCY - Hamangau, Maureen Rosanti; Suartha, I Nyoman; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2023)
This study aim to determine the praesen status which includes body temperature, frequency of respiration, frequency of heart rate and frequency of pulse in female bali cattle with gestational age in the third semester of pregnancy, namely gestational age of 7 months, 8 months and 9 months and to determine the effect of gestational age on the praesen status. The study was conducted at the Bali Cattle Breeding Center in Sobangan village Mengwi District Badung Regency used completely randomized design where gestational age was the group to be studied and analysis data was carried out using Analysis of Variance. The results showed that body temperature at 7, 8 and 9 months of gestation were 38,12 + 0,94; 38,16 + 0,50 dan 38,37 + 0,98. The frequency of respiration at 7, 8 and 9 months of gestation were 17,71 + 3,34; 19,05 + 3,22 and 20,87 + 4,86. The heart rate at 7, 8 and 9 months of gestation were 85,22 + 12,19 and 85,44 + 15.37 and 92,23 + 12,78. The pulse frequency at 7, 8 and 9 months of gestation were78,39 + 10,37; 81,57 + 10,73 and 88,18 + 13,01; Statistical analysis shown that there were significant differences (p<0,05) in body temperature, respiration frequency, heart rate and pulse rate at 7, 8 and 9 months of gestation. The conclusion is that gestational age affects praesen status which includes body temperature, frequency of respiration, frequency of heart rate and frequency of pulse rate in bali cattle at the third trimester of pregnancy. It is necessary to do research on the praesen status before parturition occurs.